Attitudes and Behaviors of Fourth Year Students on Media at Sta. Cruz South District Sta. Cruz, Zambales - Besing, Mae M. (International Journal of Multidisciplinary: Applied Business and Education Research, 2023)
This study was designed to determine the attitudes and behaviors of fourth year students on Media in Sta. Cruz District Sta. Cruz, Zambales school year 2014- 2015. It attempted to answer the following specific problems: How the respondents may be described in relation to the following attributes such as age, gender, parents’ occupation, and monthly income? How do respondents describe their attitudes and behavior in using media in terms of: Television, Radio, Internet/Face book/ Twitter/ Computer, Newspaper/ Magazines and Cell phone? Is there any significant relationship on the attitudes and behaviors of fourth year students on Media? How may the findings of the study be used as a basis for the next parallel study? The descriptive type of research was used in this study where fifty percent (50%) of the total population, four hundred forty three (443) served as respondents in assessing the attitudes and behaviors of fourth year students. The survey- questionnaire was the main instrument in gathering the data for this study. The questionnaire is divided into various parts. Data were gathered and tested through statistical tools: percentage; weighted mean; Anova. Based from the findings the researcher concluded the following: There were 226 respondents who belong to 15 years of age because it is the actual age of a fourth year student. Majority of the respondents were female because there are more female enrollees rather than male. There were 236 parents of respondents who earns P7, 000 and below. Majority of them were Farmers. Based on the conclusion, the following are hereby recommended: Proper supervision of parents to their children every time they are exposing to media. Increase children‘s engagement and interest in other activities that expand their imagination and develop their ability to solve problems. Set limits on how often, and how long, your children may play video games or view television or movies. Monitor your children’s on-line activity, social media and use of different applications. Use password protection features to limit your children’s access to electronic devices. The schools administrators must emphasize the policies about electronic devices whether it will be allowed to bring this in the school. The school administrators conduct a series of seminars, trainings and workshops about the responsible use of media. Parallel study related to the topic.